Penelitian Konsep Buku Aktivitas Untuk Pasangan - Lydia Susanto; Shienny Sutanto (Jurnal Vicidi, 2017)
This research was conducted in order to develop an activity book for teenage couples to have a healthy dating style. As an initial step in developing the book, the authors conducted a study to determine the attractiveness of the product to the target market. The method used is a combination of primary and secondary, where the research was done by quantitative, qualitative and literature studies. Through this research, it is expected that activity book for couples will had great feedback for the future so that the value of the book can be channeled properly.